Stringent fasting conditions of Mahavir Swami - Temples of India Project Team (Jio Institute, 2024)
The story of the painting in the inner/upper circle in the ceiling of the mandapa (pillared hall) revolves around Mahavir Swami's stringent fasting conditions, which required specific circumstances for accepting food. Chandanbala, formerly known as Princess Vasumati, fulfilled these conditions despite enduring hardships as a slave after being separated from her royal family. The haveli (mansion) in which the princess is depicted sitting reflects significant European architectural influence. Mistreated by a merchant’s wife, Chandanbala’s compassionate nature led her to offer lentils to Mahavir Swami, breaking his prolonged fast. This act of devotion resulted in her liberation from chains and being adorned with celestial riches. Recognized as Princess Vasumati, she was warmly received back into royalty by King Shaitanik and Queen Mrugavati, eventually receiving spiritual initiation from Mahavir Swami. The inscription reads, ‘Chandanbal Mahavir Shwami.’